ROLE AND FUNCTIONS OF FOREIGN DIRECT INVESTMENTS IN THE UZBEKISTAN ECONOMY - Ilmiy rahbar: Ashirova Gulchehra; Tayyorladi: Gulnoza Ibragimova; Jasmina Xolmurotova; Sabrina Xazratqulova; Feruza Hasanova (Modern American Journals, 2025)
This article provides an in-depth analysis of the role, significance, and functions of foreign direct investment (FDI) in the economic and social development of the Republic of Uzbekistan. Foreign investments, particularly FDI, serve as a vital tool for the country's progress and are considered an integral part of the modern economy. The article examines the volume of foreign capital attracted to Uzbekistan, its main directions, as well as its distribution from both a geographical and sectoral perspective. Furthermore, it analyzes the contribution of FDI to economic growth using statistical data and practical examples.
Keywords: Foreign direct investments (FDI), GDP, Special Economic Zones (SEZ), BIT, EBRD, WDI, Consumer Price Index (CPI), purchasing power parity (PPP), International Finance Corporation (IFC).